Level of agreement between two asthma control questionnaires in children and adolescents - Cláudio Luiz Castro Gomes de Amorim; Karina Couto Furlanetto; Thaila Corsi; Fabio Pitta (Jornal Brasileiro de Pneumologia)
ABSTRACT Objective: To investigate the level of agreement between the GINA questionnaire and the Asthma Control Test (ACT) in children and adolescents with asthma, as well as to compare the clinical, laboratory, and spirometric characteristics of patients with controlled and uncontrolled asthma as assessed by the two questionnaires. Methods: Children and adolescents with asthma had their level of asthma control cross-sectionally assessed by the GINA questionnaire and the ACT, the Childhood ACT (C-ACT) being used for the children in the sample. The participating patients also underwent spirometry, clinical assessment (for passive smoking, asthma severity, medication use, and type of inhaler device used), and laboratory measurements of vitamin D levels, blood eosinophils, and total IgE. Results: A total of 76 patients were assessed. Of those, 62% were male, and the mean age was 10 [9-12] years. In addition, 42% and 20% were classified as having uncontrolled asthma by the GINA questionnaire and the C-ACT/ACT, respectively. There was moderate agreement between the two questionnaires regarding identification of controlled and uncontrolled asthma (k = 0.505; p < 0,0001). The patients classified as having uncontrolled asthma by the GINA questionnaire had worse results in terms of daily inhaled corticosteroid dose, asthma severity, passive smoking, and spirometric parameters (FVC, FEV1, and FEF25-75%). However, there was no significant difference between patients classified as having controlled or uncontrolled asthma by the C-ACT/ACT. Conclusions: In children and adolescents with asthma, the level of agreement between the GINA questionnaire and the C-ACT/ACT appears to be moderate. The GINA questionnaire appears to have a stronger association with functional parameters, indicating better clinical assessment with less underreporting of uncontrolled asthma.